Evaluation of Nesfatin–1 levels in ewes with pregnancy toxemia - Ömer Yaprakci; Tuğra Akkuş (Revista Científica)
The goal of the present research was to investigate the effects of pregnancy toxemia (PT) on nesfatin–1 levels in ewes and to examine its relationship with spexin, another biomarker involved in energy metabolism. The study was conducted on 45 Awassi ewes that had given birth at least once and were between 120 and 150 days of pregnancy. There were three groups of ewes. The control group (Group 1, n=15) consisting healthy ewes showing β– hydroxybutyric acid (BHBA) levels < 0.8 mmol·L-1, the subclinical PT group (Group 2, n=15) involved ewes with BHBA levels between 0.8 to 2.5 mmol·L-1, and the clinical PT group (Group 3, n=15) contained ewes with BHBA levels > 2.5 mmol·L-1 (which ranged from 2.6 to